Rubella antibody levels in the healthy Chinese population: a meta-analysis - Yaning Zhuo; Zhaojun Lu; Xuechao Zhang; Xiaoping Zhang; Yingying Yang; Jiayin Han; Jian Du; Yuyang Xu; Yan Liu; Chuanxi Fu (Frontiers in Immunology, 2024)
ObjectivesTo gain a comprehensive understanding of rubella seroprevalence in the healthy population in China and to offer data-driven support for the goal of rubella elimination.MethodsCNKI, Wanfang database, VIP database, CBM, PubMed, web of Science, and Embase databases were searched to collect studies reporting the positive rate of rubella antibody among the Chinese healthy populations between 2001 and 2022. We conducted a meta-analysis using R language, and data were combined using random effects model.ResultsA total of 97 studies were included, encompassing a sample size of 103,018. Meta-analysis showed that the overall prevalence of rubella antibody positivity in the Chinese healthy population was 77.29% (95% CI: 75.26-79.33). The prevalence of rubella antibody varied significantly based on age and vaccination status. Among the age groups studied, the <1-year-old group exhibited the lowest positivity rate for rubella antibody at 47.87% (95% CI: 41.53-54.21),while the ≥50 years old group showed the highest positivity rate at 85.43% (95% CI: 81.01-89.85); individuals with a history of vaccination demonstrated a higher antibody positivity rate compared to those without vaccination history.ConclusionsThe prevalence of rubella antibody in healthy Chinese population is relatively low. In order to establish a solid immunity threshold levels, it requires conducting timely immunization programs on key groups such as middle school students and the women of childbearing age on the basis of ensuring a high level of rubella-containing-vaccines (RCV) coverage, so as to achieve the goal of eliminating rubella.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024607949.